Annual Endovascular Thrombectomy Case Volume and Thrombectomy-capable Hospitals of Korea in Acute Stroke Care - Park, Eun Hye; Hwang, Seung-sik; Oh, Juhwan; Kim, Beom-Joon; Bae, Hee-Joon; Yang, Ki-Hwa; Choi, Ah-Rum; Kang, Mi-Yeon; Subramanian, S.V. (Journal of preventive medicine and public health, 2023)
Objectives: Although it is difficult to define the quality of stroke care, acute ischemic stroke (AIS) patients with moderate-to-severe neurological deficits may benefit from thrombectomy-capable hospitals (TCHs) that have a stroke unit, stroke specialists, and a substantial endovascular thrombectomy (EVT) case volume.Methods: From national audit data collected between 2013 and 2016, potential EVT candidates arriving within 24 hours with a baseline National Institutes of Health Stroke Scale score ≥6 were identified. Hospitals were classified as TCHs (≥15 EVT case/y, stroke unit, and stroke specialists), primary stroke hospitals (PSHs) without EVT (PSHs-without-EVT, 0 case/y), and PSHs-with-EVT. Thirty-day and 1-year case-fatality rates (CFRs) were analyzed using random intercept multilevel logistic regression.Results: Out of 35 004 AIS patients, 7954 (22.7%) EVT candidates were included in this study. The average 30-day CFR was 16.3% in PSHs-without-EVT, 14.8% in PSHs-with-EVT, and 11.0% in TCHs. The average 1-year CFR was 37.5% in PSHs-without-EVT, 31.3% in PSHs-with-EVT, and 26.2% in TCHs. In TCHs, a significant reduction was not found in the 30-day CFR (odds ratio [OR], 0.92; 95% confidence interval [CI], 0.76 to 1.12), but was found in the 1-year CFR (OR, 0.84; 95% CI, 0.73 to 0.96).Conclusions: The 1-year CFR was significantly reduced when EVT candidates were treated at TCHs. TCHs are not defined based solely on the number of EVTs, but also based on the presence of a stroke unit and stroke specialists. This supports the need for TCH certification in Korea and suggests that annual EVT case volume could be used to qualify TCHs.